2006
DOI: 10.1128/jcm.01916-06
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Ofloxacin Resistance in Mycobacterium tuberculosis Clinical Isolates from China as Determined by gyrA Mutation Analysis Using Denaturing High-Pressure Liquid Chromatography and DNA Sequencing

Abstract: A high rate of double point mutations in gyrA (56% of 87 ofloxacin-resistant Mycobacterium tuberculosis clinical isolates) indicates the emergence of fluoroquinolone resistance. This is the first report to describe denaturing high-pressure liquid chromatography analysis of mutations in gyrA of M. tuberculosis in a large number of clinical isolates.Up to the present, fluoroquinolones have been studied as a first-line treatment for tuberculosis (9). However, fluoroquinolone resistance among Mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 12 publications
7
47
2
Order By: Relevance
“…We propose that the relative proportions of resistant and susceptible clones or the number of different resistant clones present in a sputum isolate reflects different stages in the progression toward clonal resistance. This conclusion differs from a previous report which suggested that multiple mutations in the QRDR lead to higher levels of resistance (32). An alternative explanation could be that of laboratory crosscontamination.…”
Section: Discussioncontrasting
confidence: 56%
“…We propose that the relative proportions of resistant and susceptible clones or the number of different resistant clones present in a sputum isolate reflects different stages in the progression toward clonal resistance. This conclusion differs from a previous report which suggested that multiple mutations in the QRDR lead to higher levels of resistance (32). An alternative explanation could be that of laboratory crosscontamination.…”
Section: Discussioncontrasting
confidence: 56%
“…19,21,42,46 Heteropeaks in fluoroquinolone-resistant M. tuberculosis have been described in detail previously. 48 In contrast to most bacteria, M. tuberculosis acquisition of drug resistance does not occur as a result of horizontal transfer of resistance-bearing genetic elements.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…c Substitutions GyrA Ala74Ser and Ala90Gly, and GyrB Gly470Ala, Asn499Lys and D644-645 were never observed independently. 18,21,26,33,42,46,47 Systematic review 827 JAC …”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of these assays target both gyrA and gyrB genes, the majority of genotypic tests target only QRDR of gyrA gene for simplicity and acceptable levels of sensitivity. The genotypic tests that have been developed include PCR-DNA sequencing [83][84][85], PCR-single strand conformation polymorphism [101], temperature-mediated heteroduplex analysis by using denaturing high-pressure liquid chromatography (HPLC) [102], pyrosequencing [103], microchip array [104], locked nucleic acid probe real-time PCR [105], multiplex PCR amplimer conformation analysis [89] and both, in-house developed as well as commercially available line probe assays [92,96,97]. The FQs are an important component of the therapy regimens for patients with MDR-TB or XDR-TB since their inclusion greatly improves treatment outcome.…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 99%